Pengaruh Layanan Penguasaan Konten Teknik Sosiodrama Terhadap Perilaku Asertif Siswa dengan Guru SMA Negeri 3 Magelang Tahun Ajaran 2015/2016 - Pambudi, Aji Taufiq; Supriyo, Supriyo (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
This study was conducted based on the phenomenon in SMA 3 Magelang which indicate that there are students who have a low assertive behavior. The research was conducted on July 28 to September 2, 2015. This study aims to determine students' assertive behavior before and after the service, and to know the influence of the control service content sociodramas techniques in improving assertive behavior class XI MIA 1. The type of research is experimental research. Methods of data collection using the instrument scale psychological scale assertive capability. Methods of data analysis using descriptive percentages and t-test. The results showed that the percentage of early before getting services at 55.99% and after getting treatment showed a percentage of 83.54% is thus increased by 27.55%. Results of t-test showed that the values ​​obtained tcalculated = 17.00> ttable = 2.00 at the 5% significance level, the calculation of the t-test showed that tcalculated> t ttable, so that Ho refused and Ha accepted. Based on the results of this study concluded that the assertive behavior class XI MIA 1 at SMA 3 Magelang before getting services with lower category, after getting the service with high category, so that assertive behavior through mastery of content services sociodrama technique can be improved.